2022
DOI: 10.1038/s41598-022-21836-7
|View full text |Cite|
|
Sign up to set email alerts
|

Plasmidome in mcr-1 harboring carbapenem-resistant enterobacterales isolates from human in Thailand

Abstract: The emergence of the mobile colistin-resistance genes mcr-1 has attracted significant attention worldwide. This study aimed to investigate the genetic features of mcr-1-carrying plasmid among carbapenem-resistant Enterobacterales (CRE) isolates and the potential genetic basis governing transmission. Seventeen mcr-harboring isolates were analyzed based on whole genome sequencing using short-read and long-read platforms. All the mcr-1-carrying isolates could be conjugatively transferred into a recipient Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…To analyze the genetic relationship of the mcr -carrying E . coli isolated in this study, we conducted a phylogenomic analysis using available genomes of mcr -carrying E. coli (n = 12) isolated from patients in Thailand in another study ( Boueroy et al., 2022 ). The phylogenetic tree had two main distinct clades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the genetic relationship of the mcr -carrying E . coli isolated in this study, we conducted a phylogenomic analysis using available genomes of mcr -carrying E. coli (n = 12) isolated from patients in Thailand in another study ( Boueroy et al., 2022 ). The phylogenetic tree had two main distinct clades.…”
Section: Resultsmentioning
confidence: 99%
“…Acquired resistance genes and chromosomal mutation-mediated antimicrobial resistance genes were identified using the ResFinder 4.1 program ( Zankari et al., 2012 ) from CGE and the resistance gene identifier from the Comprehensive Antibiotic Resistance Database ( Alcock et al., 2023 ). A SNP-based phylogenetic tree was constructed to compare twelve E. coli strains isolated from patients in Thailand ( Paveenkittiporn et al., 2021 ; Boueroy et al., 2022 ) ( Supplementary Table 1 ) with the sixteen mcr-1 harboring E. coli strains from food-animal products in this study. The construction of the tree was carried out using REALPHY online tool ( Bertels et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Given this evidence, we speculated that ECSJ33 may have originated via the food chain and integrated into wastewater ( 8 , 35 , 36 ). This highlights the importance of surveillance efforts to monitor the emergence and dissemination of mcr-1 among the elderly in LTCFs, as well as the co-existence of ESBL genes such as bla TEM-135 and mcr-1 gene carrying E. coli , which have been reported globally, particularly in animal source E. coli isolates from food-producing animal in Poland located on IncX4 plasmid ( 37 ), from human in Thailand located on IncHI/IncN plasmid ( 38 ), and from human in China located on IncI2 plasmid ( 24 ). Our study identified, for the first time, the co-existence of bla TEM-135 and mcr-1 from a wastewater source isolate in E. coli in Shanghai.…”
Section: Discussionmentioning
confidence: 99%
“…Dissemination of mcr genes, conferring resistance to colistin, was first detected on IncHI2 plasmid which was also the case in our strains. In addition, the mcr-2.1 gene was identified on a IncX4 plasmid ( Falgenhauer et al, 2016 ; Boueroy et al, 2022 ). This plasmid was first identified in Denmark and is a global concern as elevated numbers of human plasmids were identified to carry colistin resistance genes ( Hasman et al, 2015 ; Elbediwi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%